Longitudinal development of cardiorespiratory fitness parameters in youth athletes: A multiyear analysis of peak aerobic power and peak exercise performance - Köble, K.; Willinger, L.; Engl, T.; Mühlbauer, F.; Huber, S.; Dettenhofer, M.; Oberhoffer, R. (International Journal of Sports Physiology and Performance, 2026)
Purpose: While the development of cardiorespiratory fitness in normally active children and adolescents is well-documented, longitudinal data on physiological adaptations to training in youth athletes remain limited. This study aimed to investigate the long-term development of cardiorespiratory fitness in young competitive athletes over a period of 2-6 years.